2013
DOI: 10.1097/01.jaa.0000431507.82701.f7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the adult with new-onset pleural effusion

Abstract: PAs play an essential role in recognizing new-onset pleural effusion in adults. This article reviews risk factors, patient assessment, diagnostic testing, initial management, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Because in the case of a transudate, aetiology and therapy are directed to the underlying congestive heart failure, cirrhosis, or nephrosis. Alternatively, exudates are usually taken as a sign of, inflammatory disorders or malignancy, leading to more extensive diagnostic procedures [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Because in the case of a transudate, aetiology and therapy are directed to the underlying congestive heart failure, cirrhosis, or nephrosis. Alternatively, exudates are usually taken as a sign of, inflammatory disorders or malignancy, leading to more extensive diagnostic procedures [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have pointed out that MPE is caused by tumor-induced angiogenesis, and some scholars have also pointed out that vascular endothelial growth factor may be an important cause of MPE by increasing vascular endothelial permeability and exudation ( 15 ). Some studies have shown that there are more than 1.5 million new patients with pleural effusion each year in the United States, and MPE caused by cancer accounts for the vast majority of such patients ( 16 , 17 ). A clinical study involving 1783 patients with MPE found that bronchial lung cancer, particularly lung adenocarcinoma, accounted for disease in 36% of cases ( 18 ).…”
Section: Discussionmentioning
confidence: 99%